2019
DOI: 10.1042/cs20180891
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in obstructive sleep apnea–hypopnea syndrome: disease-related dysbiosis and metabolic comorbidities

Abstract: Gut microbiota alterations manifest as intermittent hypoxia and fragmented sleep, thereby mimicking obstructive sleep apnea–hypopnea syndrome (OSAHS). Here, we sought to perform the first direct survey of gut microbial dysbiosis over a range of apnea–hypopnea indices (AHI) among patients with OSAHS. We obtained fecal samples from 93 patients with OSAHS [5 < AHI ≤ 15 (n=40), 15 < AHI ≤ 30 (n=23), and AHI ≥ 30 (n=30)] and 20 controls (AHI ≤ 5) and determined the microbiome composition via 16S rRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 42 publications
8
74
0
Order By: Relevance
“…A lower Prevotella-prominent enterotype in AF patients was obtained in both studies. The increase in the Ruminococcus-predominant enterotype is characteristic of AF patients, and similar results were obtained from studies of CAD [3], symptomatic atherosclerosis [33], and obstructive sleep apnea-hypopnea syndrome (OSAHS) [34]. Patients with atherosclerosis and OSAHS have risk factors similar to those of AF patients.…”
Section: Discussionsupporting
confidence: 74%
“…A lower Prevotella-prominent enterotype in AF patients was obtained in both studies. The increase in the Ruminococcus-predominant enterotype is characteristic of AF patients, and similar results were obtained from studies of CAD [3], symptomatic atherosclerosis [33], and obstructive sleep apnea-hypopnea syndrome (OSAHS) [34]. Patients with atherosclerosis and OSAHS have risk factors similar to those of AF patients.…”
Section: Discussionsupporting
confidence: 74%
“…Our redundancy analysis revealed several taxa (genera and families) associated with measures of sleep (Fig 3). Previous work [68] examining the relationship between gut microbiome composition and severity of sleep apnea–hypopnea syndrome found that a decrease in the relative abundance of Sutterella and Brevibacterium generally coincided with an increase in severity of the disease state. In congruence with these previous findings, our study found that there was a negative correlation between these genera, and the number of awakenings.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also reported that Hcy levels were associated with increased risk of severe deep and periventricular white matter lesions, contributing to poor cognitive performance (Vermeer et al, 2002), and the strong associations between increased Hcy levels and cognitive decline in patients with AD and Parkinson's disease had been confirmed (Di Meco et al, 2018;Murray and Jadavji, 2019). Some researchers hypothesized that the Hcy/lipopolysaccharide (LPS) might mediate pyroptosis in the obese adipocytes due to the GM imbalance (Laha et al, 2018), and the altered microbiome in OSAHS patients was associated with Hcy (Ko et al, 2019). Besides, LA also contributed to cognitive deterioration by triggering the release of inflammatory factors (Kaffashian et al, 2016;Hainsworth et al, 2017).…”
Section: Figure 3 |mentioning
confidence: 99%